How do SISTERS IN ISLAM struggle with perception of Muslim women in Malaysian society? - Dworska, Żaklina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Sisters in Islam are the most thriving organization working for the rights of Muslim women in Malaysia. The main activities that have been undertaken by the activists over the years are publicity and clear opposition to cases of injustice among the extremely sensitive environment such as inequality of women in Muslim society.
Keywords: Malaysian women; women`s equality; Sisters in Islam; human rights